Nilai-nilai Pendidikan Akhlak dalam Al-Quran (Kajian Tafsir Surat An-Nahl Ayat 90-97) - Erfina, Sariaji Lina; Jasmienti, Jasmienti; Kamal, Muhiddinur; Alimir, Alimir (ANWARUL, 2023)
The background of this research is that along with the times in this era of globalization, the inculcation of morals from an early age is still lacking, considering that many young people commit violations, such as fighting parents and teachers, smoking in class, skipping class, fights between students. student. Even though the government has implemented the 2013 curriculum system, which is about developing character education, it still tends towards cognitive abilities rather than towards developing the students' own character.This type of research is library research. The data sources used by researchers are primary data sources, namely Al-Quran Surah An-Nahl verses 90-97 and Tafsir al-Munir and al-Azhar. Secondary data sources are books and literature related to this research. The data collection technique that researchers used in this study was a documentation technique by collecting data on matters related to the research object in the form of books, commentaries, journals and so on. The data analysis technique uses deductive and inductive techniques.Based on the results of the research, it can be concluded that the educational values contained in surah an-Nahl verses 90-97 and according to the interpretations of al-Munir and al-Azhar are: (1) Fair is weighing equally, punishing those who are wrong, and justifying those who are wrong. Correct. Fair is divided into three, namely fair to Allah, fair to oneself and fair to others, (2) Keeping promises, Allah SWT forbids and threatens people who break agreements and Allah likens like a woman who is not sane who deciphers the threads spun that have been he spun firmly, (3) Patience, Allah SWT sees the patience of his servant by giving tests, for those who are weak will fall and for those who are strong will harvest the fruits of their patience.